Pelatihan Pengurusan Jenazah Bagi Masyarakat Desa Hasahatan Jae Kecamatan Barumun Baru Kabupaten Padang Lawas - Nur Fitryani Siregar; Lina Mayasari Siregar (Khidmat Almujtamae: Jurnal Pengabdian Masyarakat, 2023)
In several locations, the community faces problems regarding the procession of managing the corpse. The procedures for caring for, bathing and shrouding and praying for the corpse are due to never studying, never reading, no one teaching and lack of information about the process. Therefore community service activities in the form of assistance are very important to implement. Because community service is an activity that aims to help the community in several activities without expecting rewards in any form. In general, this community service program is designed by various universities in Indonesia to make a real contribution to the nation, especially in developing the welfare and progress of the Indonesian nation. Community service activities are part of the Tri Dharma of Higher Education. In this case, this activity aims to increase the professionalism and quality of community service in carrying out the obligations of Fardhu Kifayah. This activity produces assistance output in the form of improving the quality of funeral services.